PPAR-α regulates metabolic remodelling and participates in myocardial fibrosis in patients with atrial fibrillation of rheumatic heart disease - Xiaoying Hu; Daisong Jiang; Zheng Zhang; Zhenmei An (Archives of Medical Science)
Introduction This study will explore the correlation of peroxisome proliferator activated receptor-α (PPAR-α) regulation of metabolic remodelling in the myocardial fibrosis of atrial fibrillation (AF) in rheumatic heart disease.